2014
DOI: 10.4161/epi.27835
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of hypoxia inducible factor-1α-dependent expression of placental growth factor in hypoxic conditions

Abstract: (2014) Epigenetic control of hypoxia inducible factor-1α-dependent expression of placental growth factor in hypoxic conditions, Epigenetics, 9:4, 600-610,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 59 publications
2
23
0
2
Order By: Relevance
“…Both systems, a transcription factor and an epigenetic regulator, are being regulated by hypoxia [82]. Further, HIF-1α has been suggested as an epigenetic modulator determining chromatin remodeling of hypoxia-responsive elements (HREs) sites [83]. Interestingly, in this report, a marked hyperacetylation of histones H3 and H4 was observed in the placental growth factor (Plgf) intron in hypoxic conditions.…”
Section: Epigenetics and Endothelial Dysfunctionsupporting
confidence: 47%
“…Both systems, a transcription factor and an epigenetic regulator, are being regulated by hypoxia [82]. Further, HIF-1α has been suggested as an epigenetic modulator determining chromatin remodeling of hypoxia-responsive elements (HREs) sites [83]. Interestingly, in this report, a marked hyperacetylation of histones H3 and H4 was observed in the placental growth factor (Plgf) intron in hypoxic conditions.…”
Section: Epigenetics and Endothelial Dysfunctionsupporting
confidence: 47%
“…Thus, Ang-(1-7) might reduce VEGF-A expression by inhibition of MAPK signaling. HIF-1α increases VEGF-A expression and also upregulates other proangiogenic factors, such as placental growth factor (PIGF) (46). Ang-(1-7) has been confirmed to reduce the expression of the HIF-1α gene (47), which suggests that HIF-1α may be a key mediator of Ang-(1-7) in regulating angiogenesis.…”
Section: Discussionmentioning
confidence: 89%
“…PlGF is primarily secreted by FLSs in RA synovial tissue (6), and its production can be induced by hypoxia (14,37), cytokine stimulation (14), and a cell-to-cell contact with mesenchymal stem cells (14). Because RA joints are in a hypoxic condition, our recent findings on involvement of HIF-1a in the upregulation of PlGF expression through chromatin remodeling is particularly relevant to RA (37). In the present study, we identified that PlGF-1 and PlGF-2 are the major PlGF isoforms in FLSs.…”
Section: Discussionmentioning
confidence: 99%